Shadows of the Mind: A Search for the Missing Science of Consciousness - Hurtubise, Rolland (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "Shadows of the Mind: A Search for the Missing Science of Consciousness," by Roger Penrose.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Computerization; Labor Unions; Physics; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social aspects; Thinking skills